1980
DOI: 10.1111/j.1751-1097.1980.tb03797.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin Regeneration, Calcium, and the Control of the Dark Current in Vertebrate Rods

Abstract: Abstract— The dark current of retinal rods is suppressed for an extended period when their rhodopsin is bleached. An 8% bleach completely suppresses the current for 8 min and after 35 min it is fully recovered. The dark current can recover fully from a bleaching flash without any rhodopsin being regenerated. Moreover the recovery can be hastened either by lowering the activity of calcium ions surrounding the rods or by regenerating the rhodopsin. The recovery of the dark current following these bleaches showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…A variety of studies have demonstrated that the steady-state effects of bleaching adaptation which are observed in isolated retinas can be reversed by exposing the tissue to solutions containing l l-c/s retinal (Pepperberg et al, 1978;Albani et al, 1980;Perlman et al, 1982). The experiments described in the present study demonstrate that these effects produced by exogenous application of retinoids result from events occurring within the rod outer segment and shed some light on the mechanisms regulating these changes.…”
Section: Bleaching Adaptation In Isolated Rodssupporting
confidence: 57%
See 2 more Smart Citations
“…A variety of studies have demonstrated that the steady-state effects of bleaching adaptation which are observed in isolated retinas can be reversed by exposing the tissue to solutions containing l l-c/s retinal (Pepperberg et al, 1978;Albani et al, 1980;Perlman et al, 1982). The experiments described in the present study demonstrate that these effects produced by exogenous application of retinoids result from events occurring within the rod outer segment and shed some light on the mechanisms regulating these changes.…”
Section: Bleaching Adaptation In Isolated Rodssupporting
confidence: 57%
“…6). This is somewhat faster than rates observed for rod responses in skate (-20 min for total recovery, see Pepperberg et al, 1978), bullfrog (-50 min, see Perlman et al, 1982), and rat (~40 min, see Albani et al, 1980), but different methods of application and different concentrations of 11-cis retinal were used in these studies. Though no systematic effort was made to examine the dose dependency of the resensitizing effects of 11-c/s retinal, the rates of recovery of sensitivity were lower when vesicles containing less retinoid were used.…”
Section: Bleaching Adaptation In Isolated Rodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies of several isolated retina preparations suggested the workability of an electrophysiological assay for this process. These studies indicated that the formation of rhodopsin, induced by incubation of the previously bleached retina with 11-cis retinal, promotes a substantial increase in the photic sensitivity of the rods (Pepperberg et al, 1976(Pepperberg et al, , 1978Pepperberg and Masland, 1978;Albani et al, 1980). We reasoned that the measurement Of receptor sensitivity could similarly afford the analysis, within demonstrably functional photoreceptors, of the activities of putative precursors of 11-cis retinal.…”
Section: Introductionmentioning
confidence: 99%
“…TOBA and HANAWA (1985) also indicated that changes in the extracellular Ca2+ concentration altered the adaptive state of the red rods. A reduction in the extracellular Ca2+ concentration leads to a remarkable acceleration in the recovery of rod sensitivity after a flash bleaching of a substantial amount of rhodopsin (LIPTON et al, 1977;ALBANI et al, 1980). Consequently, it would seem that if the rod sensitivity is influenced by rhodopsin intermediates, changes in the extracellular Ca2 + concentration should affect the decay rate of the intermediates.…”
mentioning
confidence: 99%